Guidelines for Best Practice in the Audiological Management of Adults with Severe and Profound Hearing Loss - Turton, Laura; Souza, Pamela; Thibodeau, Linda; Hickson, Louise; Gifford, René; Bird, Judith; Stropahl, Maren; Gailey, Lorraine; Fulton, Bernadette; Scarinci, Nerina; Ekberg, Katie; Timmer, Barbra (Seminars in Hearing, 2020)
Individuals with severe to profound hearing loss are likely to present with complex listening needs that require evidence-based solutions. This document is intended to inform the practice of hearing care professionals who are involved in the audiological management of adults with a severe to profound degree of hearing loss and will highlight the special considerations and practices required to optimize outcomes for these individuals.
Keywords: severe to profound hearing loss; hearing aids; cochlear implants; guideline